2022
DOI: 10.1007/s12264-022-00930-w
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Connectome of GABAergic Neurons in the Mouse Zona Incerta

Abstract: The zona incerta (ZI) is involved in various functions and may serve as an integrative node of the circuits for global behavioral modulation. However, the long-range connectivity of different sectors in the mouse ZI has not been comprehensively mapped. Here, we obtained whole-brain images of the input and output connections via fluorescence micro-optical sectioning tomography and viral tracing. The principal regions in the input-output circuits of ZI GABAergic neurons were topologically organized. The 3D distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…First, to determine the connections between ZI and PVT, we injected the retrograde tracer 594 retroBeads into PVT of C57BL/6J mice ( Figure 1 A). We found that the retrograde labeled neurons mainly occupied the ZIR and were rarely observed in the other parts of ZI ( Figure 1 C,D), which is consistent with previous study [ 19 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…First, to determine the connections between ZI and PVT, we injected the retrograde tracer 594 retroBeads into PVT of C57BL/6J mice ( Figure 1 A). We found that the retrograde labeled neurons mainly occupied the ZIR and were rarely observed in the other parts of ZI ( Figure 1 C,D), which is consistent with previous study [ 19 ].…”
Section: Resultssupporting
confidence: 92%
“…Since the PVT is lacks of the GABAergic inhibitory neurons, the modulation of PVT function relies on inhibitory afferents for excitation and inhibition balance in neurotransmission [ 18 ]. It is noted that ZIR is one of GABAergic source to PVT [ 19 ], recent studies demonstrated that the GABAergic ZIR neurons project to PVT neurons and contribute to conditioned feeding behavior [ 6 , 20 ]. However, the roles of the ZIR–PVT pathway in nociceptive neurotransmission have not been fully addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous mapping study of input and output connections of ZI GABAergic neurons, rabies virus-enabled monosynaptic retrograde tracing has labeled many ZI-projecting cells in the SNpc and SNpr. 67 Given the fact that SN DA neurons are mainly located in the SNpc, although further cellular phenotyping of those ZI-projecting SNpc cells is lacking in that study, we would interpret that the observed ZIprojecting SNpc neurons in Yang et al (2022) are likely to be dopaminergic. In addition, previous study has suggested the existence of D1R and D2R modulation in the ZI and shown that DA injected into the medial ZI exerts a weak inhibitory effect on food intake through dominant D2R over D1R modulation.…”
Section: Discussionmentioning
confidence: 83%
“…As the most complex organ, the brain contains trillion-level neurons, glia and other types of cells with complex connectivity. It implies that the functional states of different cells vary across distant regions, requiring large-scale investigations 5 , 6 . The whole-organ mapping efforts are building the foundations for the understanding of tissue architecture at the mesoscopic level 7 .…”
Section: Introductionmentioning
confidence: 99%